2015
DOI: 10.14474/ptrs.2015.4.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between anticipatory postural adjustment of the trunk, dual tasks and physical performance with chronic stroke survivors: a pilot test

Abstract: The purpose of this study was to investigate the relationship between anticipatory postural adjustment (APA), single task, dual tasks and physical performances. The trunk muscles of APA consist of bilateral erector spinae (ES) and bilateral internal oblique (IO) adnominal muscles, during rapid stepping with the affected or unaffected leg in a sitting posture. Design: Cross-sectional study. Methods: In patients with chronic stroke, electrodes of surface electromyography (EMG) were attached on the bilateral erec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The findings were also aligned with those from a study that suggested the prioritization of balance over cognitive tasks [18]. Overall, studies show potential benefits of incorporating DTs with tests that involve motor activities (like walking/turning) because of their similarity to real-world tasks [19][20][21][22].…”
Section: Introductionsupporting
confidence: 73%
“…The findings were also aligned with those from a study that suggested the prioritization of balance over cognitive tasks [18]. Overall, studies show potential benefits of incorporating DTs with tests that involve motor activities (like walking/turning) because of their similarity to real-world tasks [19][20][21][22].…”
Section: Introductionsupporting
confidence: 73%
“…Similarly to this, in the real community, most of the activities are multi-tasked [25]. In terms of this, to perform the TUG test, lower limb muscle strength, balance, and attention span is needed [10].…”
Section: Discussionmentioning
confidence: 99%
“…and because it is difficult to produce movement without these elements, the cognitive process plays an important role in movement control. Studies show that dual-task performance that includes cognitive and gait components improve attention capacity and functional movements in those with neurological impairments [4,38]. However, depending on the environ-ment, if the cognitive process of attention and concentrations are not properly induced, this can lead to reduced gait speeds, indicating an interdependent relationship between cognitive function and gait [34].…”
Section: Discussionmentioning
confidence: 99%